Techno-Economic Evaluation of the Production of Protein Hydrolysed from Quinoa (Chenopodium quinoa Willd.) Using Supercritical Fluids and Conventional Solvent Extraction - Luis Olivera-Montenegro; Ivan Best; Alejandra Bugarin; Camila Berastein; Hugo Romero-Bonilla; Norma Romani; Giovani Zabot; Alejandro Marzano (Biology and Life Sciences Forum, 2021)
The production of quinoa protein hydrolysate (QPH) using two technologies to extract the oil and separate the phenolic compounds (PC) prior to enzymatic hydrolysis was evaluated: (1) Supercritical fluids extraction (SFE), and (2) Conventional solvent extraction (CSE). A economic evaluation and sensitivity study was performed using SuperPro Designer® 9.0 software; quinoa grain batches of 1.5 kg (laboratory) and 2500 kg (industrial scale) were considered. The results revealed that SFE allows for higher yields and the separation of PC, however, both processes are economically promising, especially when the QPH and by-products are produced on a large scale and sold at the current market price.